Towards a strategic CSR: A Brazilian case study - Angelo, Fernanda Dias; Amui, Lara Bartocci Liboni; Caldana, Adriana Cristina Ferreira; Jabbour, Charbel Jose Chiappetta [UNESP] (Emerald, 2012)
Purpose - Organisations may be considered, at the same time, either part of the problem or part of the solution for the social-environmental crisis that is occurring. To be part of the solution, they must head for a strategic management of corporate social responsibility (CSR). The objective of the present study is to identify and analyse the interfaces between theoretical models of strategic implementation of CSR and the variables and major players involved in this process. Design/methodology/approach - This is a qualitative research using a case study strategy. The company chosen for this case study has been highlighted as one of the best national companies to work for, with significant social responsibility indices. Findings - The case study found some results, such as the importance of aligning with human resource management for strategic implementation of CSR and the integrative characteristic between different workers, that are essential for this process. Originality/value - Only a few international articles discuss CSR in Brazil. The results could be useful for classes focusing on Doing business in Brazil. © Emerald Group Publishing Limited.
Keywords: Brazil; Corporate social responsibility; Environmental management; Social management; Sustainable development